2021
DOI: 10.1115/1.4049280
|View full text |Cite
|
Sign up to set email alerts
|

Forced Convective Boiling in a Vertical Annular Test Section With Seawater Coolant

Abstract: In case of some nuclear reactors, seawater is used as an emergency resource to remove the decay heat from the reactor core. This study aims to improve the understanding of boiling heat transfer with seawater coolants. Under the boiling conditions with seawater, the mass transfer of the dissolved impurities to the heated surface is expected to significantly impact the heat transfer characteristics. The focus of this experimental work is to measure the differences of the heat transfer performance between seawate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Void fraction and pressure drop measurements are obtained to understand the differences in saturated flow boiling characteristics between seawater and normal water cooled experiments. Previously, natural circulation and sub-cooled boiling studies were conducted using the same artificial seawater coolant [7,8]. Our motivation for the current, more controlled and X-ray monitored saturated flow boiling study was prompted by the two-phase flow differences observed that can be attributed to hydrodynamic and thermodynamic differences in seawater and tap water flow boiling characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Void fraction and pressure drop measurements are obtained to understand the differences in saturated flow boiling characteristics between seawater and normal water cooled experiments. Previously, natural circulation and sub-cooled boiling studies were conducted using the same artificial seawater coolant [7,8]. Our motivation for the current, more controlled and X-ray monitored saturated flow boiling study was prompted by the two-phase flow differences observed that can be attributed to hydrodynamic and thermodynamic differences in seawater and tap water flow boiling characteristics.…”
Section: Introductionmentioning
confidence: 99%